The Size of The Company is Moderating Earning Aggresiveness and Return on Asset on The Leverage - Melinda Malau (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2020)
This study aims to examine and analyze whether earning aggresiveness affects the leverage, return on asset affects the leverage, the size of the company can moderate the effect of earning aggresiveness on the leverage, the size of the company can moderate return on asset on the leverage. The sample used in the study was 500 observations using data from manufacturing companies for the period 2014-2018. The first model is without moderation variable, while the second model is with moderating variable. The results of the first model and second model show that earning aggressiveness has a significant positive effect on the leverage. Return on asset has a significant negative effect on the leverage. Size strengthens the effect of earnings aggressiveness on the leverage. Size strengthens the effect of return on asset on the leverage. In making investment decisions, investors must evaluate the quality of earnings reporting.